Evaluation of critical nitrogen and phosphorus models for maize under full and limited irrigation conditions - Djaman, Koffi; Irmak, Suat (Italian Journal of Agronomy, 2017)
Proper nitrogen (N) fertiliser application rates and timing of application, coupled with optimum irrigation management can improve the sustainability of maize production and reduce the risk of environmental contamination by nutrients. The impact of full and limited irrigation and rainfed conditions on in-season maize (Zea mays L.) shoot biomass nutrient concentration and critical N and phosphorus (P) indices were evaluated using a combination of measured nutrients and critical N and P models in south central Nebraska in 2009 and 2010. Four irrigation treatments [fully-irrigated treatment (FIT), 75% FIT, 60% FIT and 50% FIT) and rainfed] were imposed. Irrigation regimes impacted the shoot biomass N concentration. The shoot biomass N concentration was above the critical N (Ncrit) concentration throughout the growing season under FIT and 75% FIT and was below the Ncrit value for the most limited irrigation (60% FIT and 50% FIT) and rainfed treatments. Nitrogen nutrient index (NNI) varied from 0.68 to 2.0. Biomass N concentration was below Ncrit [i.e., NNI<1] from 105 days after planting (DAP) to harvest under rainfed and 50% FIT and from 114 DAP to harvest under 60% FIT. Overall, the FIT and the 75% FIT had NNI values greater than 1.0 throughout both growing seasons. Phosphorus concentration, which decreased with biomass accumulation and irrigation amounts, varied from 1.0 to 4.8 g kg–1, with FIT having the highest biomass P concentration. The critical N model combined with NNI can be used to evaluate N and P in maize for in-season nutrient diagnosis under the conditions presented in this research.